What makes individual investors exercise early? Empirical evidence from non-tradable fixed-income products - Eickholt, Mathias; Entrop, Oliver; Wilkens, Marco (Journal of Banking & Finance, 2018)
This paper studies the early exercise behavior of individual investors in non-tradable German governmental putable bonds. Analyzing holding and exercise decisions of more than 220,000 individual investors at a single-account level over 13 years, our major findings are: (i) Individual investors use their early exercise right predominantly at times that are not optimal according to standard option pricing theory. (ii) Only very few attractive exercise opportunities are exploited over time. (iii) Both exercises and failure to exercise differ significantly among investor groups, are related to their personal characteristics as well as product characteristics and environmental circumstances, and are subject to cognitive biases. They tend to be persistent over time on the investor level. (iv) The demand by investors for liquidity and financial flexibility is a more important motive for investment and exercise than performance seeking.